A Specific Blend of Drakolide and Hydroxymethylpyrazines: An Unusual Pollinator Sexual Attractant Used by the Endangered Orchid Drakaea micrantha. (12th December 2019) - Bohman, Björn; Tan, Monica M. Y.; Phillips, Ryan D.; Scaffidi, Adrian; Sobolev, Alexandre N.; Moggach, Stephen A.; Flematti, Gavin R.; Peakall, Rod
Abstract: Bioactive natural products underpin the intriguing pollination strategy used by sexually deceptive orchids. These compounds, which mimic the sex pheromones of the female insect, are emitted in particular blends to lure male insect pollinators of specific species. By combining methods from field biology, analytical chemistry, electrophysiology, crystallography, and organic synthesis, we report that an undescribed β‐hydroxylactone, in combination with two specific hydroxymethylpyrazines, act as pollinator attractants in the rare hammer orchid Drakaea micrantha . This discovery represents an unusual case of chemically unrelated compounds being used together as a sexual attractant. Furthermore, this is the first example of the identification of pollinator attractants in an endangered orchid, enabling the use of chemistry in orchid conservation. Our synthetic blend is now available to be used in pollinator surveys to locate suitable sites for plant conservation translocations. Abstract : Trügerisches Drakolid : Der neuartige Naturstoff Drakolid (3 c ) wirkt zusammen mit den beiden Hydroxymethylpyrazinen 1 und 2 als Bestäuberlockstoff in der bedrohten sexualtäuschenden Hammerorchidee Drakaea micrantha .